The Notifiction: How Push Notifications from Neighbourhood Surveillance Apps Can Create an Alternative Narrative of Place - Wright, Andy Fischer (Imaginations, 2021)
This article concerns the author’s attempt to stay connected with his home neighborhood in Austin, TX, and how that conflicts with using the neighbourhood surveillance platform Ring Neighbors during the pandemic. Utilizing a mixed methodology based in autoethnography, the author considers how the notifications produced by this platform can create new potential narratives about his neighbourhood during a pandemic. While this app is theoretically helpful by showing what community members are thinking, the notifications that it thrusts into his daily life tend to create a fictional representation of his home, which he deems a “notifiction.”